2019
DOI: 10.1111/jocd.13150
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of Demodex blepharitis in rosacea and facial demodicosis patients

Abstract: Background Rosacea is an inflammatory disease with 50% of ocular involvement rate. Primary demodicosis is an eruption caused by Demodex mites, and there is no data about the rate of ocular involvement in primary demodicosis. Aims In this cross‐sectional study, it is aimed to reveal the frequency of Demodex blepharitis in rosacea and primary demodicosis patients. Methods In total, 58 rosacea, 33 primary demodicosis patients, and 31 healthy volunteers were included in the study. Four samples were obtained from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…One study compared patients with primary demodicosis and patients with rosacea with Demodex-induced blepharitis to healthy controls and found that patients with primary demodicosis and patients with rosacea did not have significantly different ocular findings. 23 In contrast, Forton and De Maertelaer 24 reported that patients with PPR had significantly more severe ocular manifestations compared with patients with demodicosis (P=.004).…”
Section: Commentmentioning
confidence: 92%
“…One study compared patients with primary demodicosis and patients with rosacea with Demodex-induced blepharitis to healthy controls and found that patients with primary demodicosis and patients with rosacea did not have significantly different ocular findings. 23 In contrast, Forton and De Maertelaer 24 reported that patients with PPR had significantly more severe ocular manifestations compared with patients with demodicosis (P=.004).…”
Section: Commentmentioning
confidence: 92%
“…14 Standardized protocols are also needed in further research, considering the heterogeneity of product manufacturer, dosage or concentration, administration frequency, and duration. 14 Besides, D. folliculorum, Helicobacter pylori, and genetics contribute to the pathogenesis of rosacea, [47][48][49][50][51] but are not shown in these models. Animal models each can only reflect limited aspects of human rosacea.…”
Section: U Vb -Induced Modelmentioning
confidence: 94%
“…44 Thus, it is not surprising that a 2019 study found that patients presenting with papulopustular rosacea had significantly higher odds of developing Demodex blepharitis than in control patients. 46 Evidently, we always need to examine the patients' face because rosacea and Demodex blepharitis are often seen together in a clinical setting. This is especially true of childhood Rosacea.…”
Section: Diagnosismentioning
confidence: 99%